2020
DOI: 10.1016/j.heliyon.2020.e04608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maturity on the moisture sorption isotherm of chili pepper (Mareko Fana variety)

Abstract: The moisture sorption isotherm at three maturity levels of the M a reko Fana chili pepper variety (red, brown and green) has been studied in this paper. The sorption isotherm was determined based on the standard static gravimetric method using a glycerol-water mixture in a relative humidity range of 10–92% at three temperature levels and nonlinear regression analysis was used to select suitable sorption models. The Clasius - Clapeyron equation was implemented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
(64 reference statements)
2
10
0
Order By: Relevance
“…Kammoun-Bejar et al [ 32 ] found similar results for orange peels. Other authors also reported that the Peleg model offered a good fit to other more dissimilar agricultural products, such as pepper, papaya or fig [ 15 , 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kammoun-Bejar et al [ 32 ] found similar results for orange peels. Other authors also reported that the Peleg model offered a good fit to other more dissimilar agricultural products, such as pepper, papaya or fig [ 15 , 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, an accurate modelling of the sorption isotherms permits to establish the best storage conditions or the estimation of the equilibrium moisture content of the sample in the air drying conditions used and allows for the determination of both the optimum end point of drying, which preserves product quality and saves energy [ 12 , 13 ]. In fact, numerous scientific articles can be found that focus on the estimation of the sorption isotherms of very different agricultural products, such as chia, pepper, cambucci or pumpkin [ 14 , 15 , 16 , 17 ]. The experimental sorption isotherms can be determined using several methods, and the hygrometric method is one of the most commonly applied due to its simplicity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Water activity (αw), is one of the critical criteria in fruit and vegetable handling mechanism to determine microorganism development and the release of toxin that indicates non-enzymatic and enzymatic browning formation in the products. The influence of water activity on fruit and vegetable quality during drying and storage was analyzed in detail in the work of (Getahun et al, 2020a).…”
Section: Water Activitymentioning
confidence: 99%
“…In 2019, Ethiopia produced 313,000 t of dry chili peppers on 175,000 ha of land and found in 3 rd next to India, Thailand and mainland China (FAOSTAT, 2019). The most commonly grown types are the Mareko Fana and Bako Local chili varieties of capsicum Annum L. species (Musie et al, 2015, Samira et al, 2013, Getahun et al, 2020. Mareko Fana is a conical form of fruit that ripens to a dark red appearance and has a high extractable color intensity.…”
Section: Nomenclaturementioning
confidence: 99%